Induction experiences of novice teachers and their coaches. Issue 4 (8th August 2021) - Mitchell, Douglas; Keese, Jeffrey; Banerjee, Manjari; Huston, Debbee; Kwok, Andrew
ABSTRACT: This mixed-methods study explores the experiences and influence of induction on novice teachers. The authors quantitatively analyze survey data from over two thousand novice teachers and a thousand of their coaches through statistical comparisons and multiple linear regression analyses to explore whether structures of induction are associated with how teachers learn and develop in their pedagogy. Qualitative analyses of respondents' open-ended responses guided by word cluster formations indicate a positive feeling about this induction program but revealed differing areas of focus between novice teachers and their coaches. Results indicate the importance of coaches, curriculum, and the learning management system in creating positive induction experiences. Findings from this study have implications for the influence and structural design of induction programs for novice teacher development.